Penilaian Kualitas Pengendalian Internal, Kualitas Audit Internal dan Kualitas Komite Audit Berbasis COSO ERM dan PBI pada Perbankan di Indonesia - , KHALISAH VISIANA SUBEKTI, Dr. Sony Warsono, MAFIS, Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study entitled âpenilaian kualitas pengendalian internal, kualitas audit internal dan kualitas komite audit berdasarkan COSO ERM dan PBI pada perbankan Indonesiaâ. This study aims to assess the quality of internal control, internal audit quality and the quality of the audit committee based on the COSO ERM and PBI in Indonesian banking and to describe the internal control, quality of internal audit and quality of audit committee at three selected entities that are considered to represent the Indonesian banking. This study is a qualitative study using a simple quantitative method and does not use statistic. The data used for the study is qualitative data belonging to the entites that has been published. these data are annual reports of entities and other data related to the study. Based on the results of the study, showed that internal control quality, internal audit quality and audit committee quality based on the COSO ERM and Bank Indonesia Regulation on banking Indonesia has been good. Keywords: Internal Control, Internal Audit, Audit Committee